Response inhibition in children with and without ADHD after traumatic brain injury. Issue 1 (30th March 2012) - Ornstein, Tisha J.; Max, Jeffrey E.; Schachar, Russell; Dennis, Maureen; Barnes, Marcia; Ewing‐Cobbs, Linda; Levin, Harvey S.
<x xml:space="preserve">Abstract</x> Children with attention‐deficit hyperactivity disorder (ADHD) and traumatic brain injury (TBI) show deficient response inhibition. ADHD itself is a common consequence of TBI, known as secondary ADHD (S‐ADHD). Similarity in inhibitory control in children with TBI, S‐ADHD, and ADHD would implicate impaired frontal‐striatal systems; however, it is first necessary to delineate similarities and differences in inhibitory control in these conditions. We compared performance of children with ADHD and those with TBI without pre‐injury ADHD on a stop signal, response inhibition task. Participants were 274 children aged 6–14 years. There were 92 children with ADHD, 103 children with TBI, and 79 typically developing children who served as controls. Among the TBI participants, injury severity ranged from mild to severe. Children with ADHD and TBI showed deficient inhibition. The deficit in children with ADHD was as great as or greater than that in children with TBI, regardless of degree of TBI severity or the presence of S‐ADHD. The finding indicates that TBI results in deficient inhibition regardless of the development of S‐ADHD.